Strategi Inovatif untuk Meningkatkan Kunjungan dan Loyalitas Tamu di Hotel RedDoorz Makassar - Nasir Nasir (EBISMAN eBisnis Manajemen, 2025)
The hospitality industry in Makassar continues to develop along with the increasing number of domestic and foreign tourists. RedDoorz Hotel as one of the providers of budget-friendly accommodation services faces stiff competition in attracting visitors and maintaining guest loyalty. This study aims to analyze the innovative strategies implemented by Hotel RedDoorz Makassar in increasing the number of visitors and building customer loyalty. The research method used is a qualitative approach with in-depth interview techniques, observations, and secondary data analysis from company reports and customer reviews on digital platforms. The results of the study show that the use of digital promotion through social media, SEO optimization, and collaboration with online booking platforms contribute significantly to the increase in hotel occupancy rates. In addition, the implementation of loyalty programs, the provision of exclusive discounts, and excellent service play an important role in retaining guests who have stayed. The conclusion of this study confirms that an integrated digital promotion strategy and consistent customer service are the main factors in increasing guest attraction and loyalty at Hotel RedDoorz Makassar.